Transshipments through Crossdocks with Inventory and Time Windows - LIM, Andrew (Institutional Knowledge at Singapore Management University, 2005)
A major challenge in making supply meet demand is to coordinate transshipments across the supply chain to reduce costs and increase service levels in the face of demand fluctuations, short lead times, warehouse limitations, and transportation and inventory costs. In particular, transshipment through crossdocks, where just-in-time objectives prevail, requires precise scheduling between suppliers, crossdocks, and customers. In this work, we study the transshipment problem with supplier and customer time windows where flow is constrained by transportation schedules and warehouse capacities. Transportation is provided by fixed or flexible schedules and lot-sizing is dealt with through multiple shipments. We develop polynomial-time algorithms or, otherwise, provide the complexity of the problems studied.